Sangpradubina, an astonishing new mayfly genus from Thailand (Ephemeroptera: Leptophlebiidae: Atalophlebiinae) - Boonsoong, Boonsatien; Sartori, Michel (Zootaxa, 2016)
A newly discovered representative of Leptophlebiidae is described and illustrated from Thailand as Sangpradubina thailandica, gen. nov. and sp. nov., based on larvae and reared adults. This new species presents an interesting transitional position, being close to Choroterpes s.l. in the winged stages, but closer to Thraulus s.l. in the nymphal stage. Nymphs are differentiated from those of all genera of the Thraulus lineage by the combination of gill I consisting of only a single and slender lamella, gills II–VII being fimbriate only in the distal half, each mandible having a tuft of setae only in the middle of the lateral margin, each maxilla having a well-developed anterolateral projection, fore- and middle femora each having a row of long setae on the outer margin, as well as tarsal claws having 4 denticles at the base and 9 in the apical position. Adults of the new genus barely differ from any genera of the Choroterpes lineage. The egg chorionic structure of Sangpradubina also appears to be unusual in that KCT’s are concentrated on one pole.